17β-Estradiol Abrogates Oxidative Stress and Neuroinflammation after Cortical Stab Wound Injury - Kamran Saeed; Myeung Hoon Jo; Jun Sung Park; Sayed Ibrar Alam; Ibrahim Khan; Riaz Ahmad; Amjad Khan; Rahat Ullah; Myeong Ok Kim (MDPI AG, 2021)
Disruptions in brain energy metabolism, oxidative damage, and neuroinflammation are commonly seen in traumatic brain injury (TBI). Microglial activation is the hallmark of neuroinflammation. After brain injury, microglia also act as a double-edged sword with distinctive phenotypic changes. Therefore, therapeutic applications to potentiate microglia towards pro-inflammatory response following brain injury have become the focus of attention in recent years. Here, in the current study, we investigated the hypothesis that 17β-estradiol could rescue the mouse brain against apoptotic cell death and neurodegeneration by suppressing deleterious proinflammatory response probably by abrogating metabolic stress and oxidative damage after brain injury. Male C57BL/6N mice were used to establish a cortical stab wound injury (SWI) model. Immediately after brain injury, the mice were treated with 17β-estradiol (10 mg/kg, once every day via i.p. injection) for one week. Immunoblotting and immunohistochemical analysis was performed to examine the cortical and hippocampal brain regions. For the evaluation of reactive oxygen species (ROS), reduced glutathione (GSH), and oxidized glutathione (GSSG), we used specific kits. Our findings revealed that 17β-estradiol treatment significantly alleviated SWI-induced energy dyshomeostasis and oxidative stress by increasing the activity of phospho-AMPK (Thr172) and by regulating the expression of an antioxidant gene (Nrf2) and cytoprotective enzymes (HO-1 and GSH) to mitigate ROS. Importantly, 17β-estradiol treatment downregulated gliosis and proinflammatory markers (iNOS and CD64) while significantly augmenting an anti-inflammatory response as evidenced by the robust expression of TGF-β and IGF-1 after brain injury. The treatment with 17β-estradiol also reduced inflammatory mediators (Tnf-α, IL-1β, and COX-2) in the injured mouse. Moreover, 17β-estradiol administration rescued p53-associated apoptotic cell death in the SWI model by regulating the expression of Bcl-2 family proteins (Bax and Bcl-2) and caspase-3 activation. Finally, SWI + 17β-estradiol-treated mice illustrated reduced brain lesion volume and enhanced neurotrophic effect and the expression of synaptic proteins. These findings suggest that 17β-estradiol is an effective therapy against the brain secondary injury-induced pathological cascade following trauma, although further studies may be conducted to explore the exact mechanisms.